Foreign Bodies in the Esophagus - Wattanarungsan, Panya (Journal of Health Science of Thailand, 2018)
Ingested foreign bodies were commonly diagnosed in clinical practice. Success of removal depended on appropriate management. Delayed diagnosis and removal of these foreign bodies could lead to life-threatening complications. This retrospective study reviewed clinical histories of all patients admitted at Paholpolpayuhasena hospital from January 2003 to December 2007. The goals of study were to identify a type and site of the ingested foreign bodies, to examine sensitivity and specificity of plain film in diagnosis of ingested foreign bodies, and to review clinical management and complications. The results revealed that 71 of 90 patients (78.9%) were diagnosed with ingested foreign bodies. Of the 71 patients, thirty-nine cases (54.9%) were male and thirty-two cases (45.1%) were female. Thirty-four patients were children and thirty-seven patients were adult. The most common foreign bodies were coins (45.1%), fish bones (23.9%), and chicken bones/bone of other animals (16.9%) respectively. Most of the foreign bodies were found in the cervical esophagus (88.8%). Plain film of neck showed sensitivity and pecificity (88.7% and 89.5% respectively) indicating that about 88.7 percent of patients with abnormal plain film of neck can have ingested foreign bodies while 89.5 percent of patients with normal plain film of neck can be normal. Rigid esophagoscopy was an appropriate approach for removal of foreign bodies without any serious complications. In conclusion, plain film of neck was useful in diagnosis of ingested foreign bodies. Rigid esophagoscopy was reliable and safe method in the treatment of esophageal foreign bodies.